1988
DOI: 10.1507/endocrj1954.35.57
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Uterine Estrogen Receptor Concentrations in Persistent Estrous and Persistent Diestrous Rats.

Abstract: Changes in uterine weight and the estrogen receptor concentrations were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…al., 1981) (Puri et al, 1982;Renoir et al, 1982;Grandics et al, 1984;Atrache et al, 1985;Redeuilh et al, 1987). Kd and NBSmax values observed in both cytosolic and nuclear receptor fraction in this study are not much different from those of the ERs already reported in the rodent uterus (Aihara et al, 1980(Aihara et al, , 1988Evans et al, 1980;Chuknyiska et al, 1984Chuknyiska et al, , 1985.…”
Section: Discussioncontrasting
confidence: 68%
“…al., 1981) (Puri et al, 1982;Renoir et al, 1982;Grandics et al, 1984;Atrache et al, 1985;Redeuilh et al, 1987). Kd and NBSmax values observed in both cytosolic and nuclear receptor fraction in this study are not much different from those of the ERs already reported in the rodent uterus (Aihara et al, 1980(Aihara et al, , 1988Evans et al, 1980;Chuknyiska et al, 1984Chuknyiska et al, , 1985.…”
Section: Discussioncontrasting
confidence: 68%
“…A K d value of 13.74 ± 6.735 nM for E 2 -binding sites obtained in the present study seems to be high in comparison with the dissociation constant of high affinity estrogen receptor reported in vertebrates, such as in mouse uterus (0.23 nM, Aihara et al, 1980;1.4 nM, Horigome et al, 1987), rat uterus (0.092-0.104 nM, Aihara et al, 1988). However, higher dissociation constant has also been reported in Atlantic salmon liver (13 K d , Lazier et al, 1985) along with a much lower affinity-binding site.…”
Section: Nature Of Specific [ 3 H] E 2 -Binding Sites In the Fatbodysupporting
confidence: 55%
“…In contrast, wet weight and ovary and uterus indices were significantly lower in the estradiol and triptorelin groups than in the control group. In a previous study, ovarian and uterine weights of persistent oestrus- or dioestrus-cycle rats were lower than those of rats with normal oestrus cycles [ 31 ]. Long-term estradiol or triptorelin administration may change the oestrus cycle of rats from normal to a persistent cycle of oestrus and dioestrus.…”
Section: Discussionmentioning
confidence: 99%